Nanoscale positive electrode material precursor and preparation method and application thereof

The precursor of nano-scale positive electrode material is prepared by spray pyrolysis, which solves the problem of poor contact between the positive electrode and the solid electrolyte in solid-state batteries, significantly improves the battery's conductivity and lithium ion transmission rate, and improves battery performance.

CN119551741AActive Publication Date: 2025-03-04JINGMEN GEM NEW MATERIAL CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411825866.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-04
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

Traditional lithium-ion batteries are caused by the toxic, flammable and safety hazards caused by the penetration of lithium dendrites of liquid batteries. In addition, the interface contact between the positive electrode and the solid electrolyte in solid batteries is poor, which affects ion transmission.

Method used

The nano-scale positive electrode material precursor was prepared by spraying sprayed with a spray head, and the mixed metal salt solution was performed in the upper, middle and lower temperature zones of the pyrolysis furnace, and the temperature gradient was controlled to obtain a nano-scale positive electrode material precursor with a particle size of less than 100 nm.

Benefits of technology

The contact between the positive electrode and the solid electrolyte is improved, the conductivity and lithium ion transmission rate are improved, the material activity and capacity are improved, and the overall performance of the solid-state battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551741A_ABST
    Figure CN119551741A_ABST
Patent Text Reader

Abstract

The invention discloses a nanoscale positive electrode material precursor as well as a preparation method and application thereof. A spray pyrolysis device is adopted for preparing the nanoscale all-solid-state battery positive electrode material, the spray pyrolysis device comprises a pyrolysis furnace, a spray head is arranged at the top of a hearth of the pyrolysis furnace, and a product outlet is formed in the bottom of the pyrolysis furnace; the pyrolyzing furnace is divided into an upper temperature area, a middle temperature area and a lower temperature area which are independently controlled in temperature from top to bottom; the preparation method comprises the following steps that a mixed metal salt solution is sprayed through a spray head, atomized liquid drops enter a pyrolyzing furnace to be subjected to spray pyrolysis, and the temperature of an upper temperature area is controlled to be t1lt; the temperature of the medium-temperature area is t2lt; the temperature of the lower temperature zone is t3, and obtaining the nanoscale positive electrode material precursor after spray pyrolysis. When the positive electrode material prepared from the nanoscale positive electrode material precursor is applied to a solid-state battery, the contact property of a positive electrode and a solid-state electrolyte can be improved, the conductivity and the lithium ion transmission rate are greatly improved, and the performance of the solid-state battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a nano-scale positive electrode material precursor and a preparation method and application thereof. Background Art

[0002] As a simple and efficient energy storage system, lithium-ion batteries have received great attention at all levels of modern energy technology development. However, traditional liquid batteries have toxic and flammable problems due to the use of organic electrolytes. In addition, lithium dendrites penetrate the diaphragm and cause internal short circuits in the battery, posing safety risks such as flammability and explosion. Therefore, replacing the electrolyte and diaphragm in traditional lithium-ion batteries with solid electrolytes and developing safe and high-performance low-cost all-solid-state batteries has become a major challenge in the world's energy field today.

[0003] The main problem of solid-state batteries is the interface contact problem. The positive electrode and the solid electrolyte cannot contact well, which affects the ion transport. Therefore, it is important to prepare nanoscale positive electrode material precursors to facilitate the contact between the positive electrode and the solid electrolyte.

[0004] At present, most companies use the coprecipitation method to prepare precursors. For example, CN116253368A, CN107706364A, and CN115215388A all use the coprecipitation method to prepare cathode material precursors. However, the coprecipitation method has high energy consumption, low yield, high wastewater, and large particle size of the prepared precursor. It is not conducive to good contact between the cathode and the solid electrolyte in solid-state batteries.

[0005] Therefore, providing a nanoscale positive electrode material precursor so that it can be used in solid-state batteries to improve the contact between the positive electrode and the solid electrolyte is a technical problem that needs to be solved urgently. Summary of the invention

[0006] In view of the above technical problems existing in the prior art, the object of the present invention is to provide a nanoscale positive electrode material precursor and a preparation method and application thereof.

[0007] In the present invention, the "nanoscale" in the nanoscale positive electrode material precursor refers to that the secondary particle size of the positive electrode material precursor is less than 100 nm.

[0008] To achieve the above object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a nano-scale positive electrode material precursor, wherein a spray pyrolysis device is used to prepare a nano-scale positive electrode material for an all-solid-state battery, wherein the spray pyrolysis device comprises a pyrolysis furnace, and a nozzle is arranged on the top of the furnace of the pyrolysis furnace; the pyrolysis furnace is divided from top to bottom into an upper temperature zone, a middle temperature zone and a lower temperature zone with independent temperature control;

[0010] The preparation method comprises the following steps:

[0011] The mixed metal salt solution is sprayed through a nozzle, and the atomized droplets enter a pyrolysis furnace for spray pyrolysis. The temperature of the upper temperature zone is controlled to be t1 < the temperature of the middle temperature zone t2 < the temperature of the lower temperature zone t3. After spray pyrolysis, a nano-scale positive electrode material precursor is obtained.

[0012] The method of the present invention prepares a nano-scale positive electrode material precursor by using a spray pyrolysis method, and the spray entering from the top sequentially experiences an upper temperature zone, a middle temperature zone and a lower temperature zone under the action of gravity, and the temperature of the spray pyrolysis is increased, so that a nano-scale positive electrode material precursor can be obtained. Since the particle size of the positive electrode material precursor is small, the positive electrode material prepared by using it can be applied to a solid-state battery to improve the contact between the positive electrode and the solid electrolyte, greatly improve the conductivity and lithium ion transmission rate, improve the material activity and capacity, and improve the performance of the solid-state battery.

[0013] The method of the present invention simplifies the production process, the preparation method is pollution-free, the preparation time is short, the output is large, the cost is low, and it is suitable for large-scale production. Moreover, the prepared positive electrode material precursor has a small particle size and a narrow particle size distribution. Moreover, the preparation method of the present invention is suitable for doping nano-scale positive electrode material precursors, and the doping is easy and the element distribution uniformity is good.

[0014] In the present invention, the upper temperature zone, the lower temperature zone and the lower temperature zone are interconnected areas, each area is independently temperature controlled, and the temperature of each area refers to the temperature at the center of the corresponding area. In practice, the temperature at the center of the corresponding area can be tested by a temperature sensor.

[0015] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0016] Preferably, t2-t1 is 200°C to 300°C, for example, it may be 200°C, 220°C, 240°C, 260°C, 280°C or 300°C.

[0017] Preferably, t3-t2 is 200°C to 400°C, for example, it may be 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 325°C, 350°C, 375°C or 400°C.

[0018] By limiting the temperature difference between adjacent zones, it is more conducive to reducing the particle size of the nano-scale positive electrode material precursor.

[0019] Preferably, the temperature t1 of the upper temperature zone is 400°C to 500°C, for example, it may be 400°C, 420°C, 450°C, 460°C, 480°C or 500°C.

[0020] Preferably, the temperature t2 of the medium temperature zone is 700°C to 800°C, for example, it may be 700°C, 720°C, 725°C, 750°C, 760°C, 770°C, 780°C or 800°C.

[0021] Preferably, the temperature t3 of the lower temperature zone is 1000°C to 1300°C, for example, it may be 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C or 1300°C.

[0022] Preferably, the ratio of the heights of the upper temperature zone, the middle temperature zone and the lower temperature zone is (1-1.5):(2-4):(1-1.5), wherein the selection range of the height of the upper temperature zone is "1-1.5", for example, it can be 1, 1.1, 1.2, 1.3, 1.4 or 1.5, etc.; the selection range of the height of the middle temperature zone is "2-4", for example, it can be 2, 2.2, 2.5, 2.6, 2.7, 2.8, 3, 3.3, 3.5, 3.6, 3.8 or 4, etc.; the selection range of the height of the lower temperature zone is "1-1.5", for example, it can be 1, 1.1, 1.2, 1.3, 1.4 or 1.5, etc.

[0023] By limiting the temperature t1 of the upper temperature zone, the temperature t2 of the middle temperature zone and the temperature t3 of the lower temperature zone within the above range and controlling the height ratio of the upper temperature zone, the middle temperature zone and the lower temperature zone, it is more conducive to reducing the particle size of the nano-scale positive electrode material precursor.

[0024] Preferably, the mixed metal salt solution is a ternary mixed salt solution of nickel, cobalt and manganese, and the concentration of the mixed metal salt solution is 100g / L to 150g / L, for example, it can be 100g / L, 105g / L, 110g / L, 115g / L, 120g / L, 125g / L, 130g / L, 135g / L, 140g / L, 145g / L or 150g / L, etc.

[0025] In one embodiment, the nickel-cobalt-manganese ternary mixed salt solution is obtained by dissolving nickel salt, cobalt salt and manganese salt in a solvent. The present invention does not specifically limit the types of nickel salt, cobalt salt and manganese salt, including but not limited to at least one of sulfate, nitrate, chloride or nitrate, and the selection of nickel salt, cobalt salt and manganese salt is independent and does not affect each other.

[0026] Preferably, the spray volume of the nozzle is 50mL / min to 100mL / min, for example, it can be 50mL / min, 55mL / min, 60mL / min, 65mL / min, 70mL / min, 75mL / min, 80mL / min, 85mL / min, 90mL / min, 95mL / min or 100mL / min, etc.

[0027] Preferably, the angle of the nozzle is 30° to 120°, for example, 30°, 40°, 45°, 50°, 60°, 70°, 80°, 90°, 95°, 100°, 110° or 120°. In the present invention, the angle of the nozzle refers to the maximum coverage angle of the droplets sprayed by the nozzle. The nozzle is set in the direction directly downward. If the angle of the nozzle is too small, the sprayed droplets are too large and the calcination is incomplete; if the angle of the nozzle is too large, it is easy to adhere to the pipe wall.

[0028] Preferably, under the action of pressure, the mixed metal salt solution enters the nozzle to be sprayed, and the feed pressure is 0.2MPa to 0.6MPa, for example, it can be 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa or 0.6MPa.

[0029] The spray pyrolysis device also includes an air compressor, which is connected to a liquid storage bottle and the nozzle, respectively. The liquid storage bottle is used to hold a mixed metal salt solution. A first valve is provided on the pipeline of the air compressor and the liquid storage bottle, and a second valve is provided on the pipeline of the air compressor and the nozzle. The atomization degree of the mixed metal salt solution can be adjusted by adjusting the first valve and the second valve. Preferably, during the spray pyrolysis process, the pressure in the furnace is -0.1MPa to -0.6MPa, for example, it can be -0.1MPa, -0.2MPa, -0.3MPa, -0.4MPa, -0.5MPa, -0.6MPa, etc. The reason and benefit of such a setting is that it can ensure that the material has good fluidity, avoid local deposition of the material, and fully react. If the negative pressure in the furnace is too high, it will easily lead to insufficient calcination time and inability to fully react to obtain oxides; if the negative pressure in the furnace is too low, first of all, it will cause the material to deposit at the bottom of the pipe, accumulate and block the pipe, requiring shutdown for unblocking, affecting productivity and cost, and secondly, the material remaining at the bottom will be heated at high temperature all the time, and the electrical performance will decrease.

[0030] Preferably, the spray pyrolysis time is 5 s to 10 s, for example, 5 s, 6 s, 7 s, 8 s, 9 s or 10 s.

[0031] In the present invention, the time of spray pyrolysis refers to the total time from the start time to the end time, wherein the start time is the time when the mixed metal salt solution is sprayed from the nozzle, and the end time is the time when the nano-scale positive electrode material precursor reaches the product outlet. The time of spray pyrolysis here is not the total time of continuous production.

[0032] In a second aspect, the present invention provides a nanoscale positive electrode material precursor prepared by the method described in the first aspect, wherein the primary particle size of the nanoscale positive electrode material precursor is in the range of 3nm to 7nm, and the secondary particle size is in the range of 30nm to 70nm.

[0033] As an example, the primary particle size can be 3nm, 4nm, 5nm, 6nm or 7nm, etc.; the secondary particle size can be 30nm, 32nm, 33nm, 35nm, 36nm, 38nm, 40nm, 43nm, 46nm, 48nm, 50nm, 52nm, 55nm, 57nm, 60nm, 62nm, 65nm, 67nm, 68nm or 70nm, etc.

[0034] In a third aspect, the present invention provides a positive electrode material, which is prepared using the nanoscale positive electrode material precursor described in the second aspect.

[0035] In a fourth aspect, the present invention provides a method for preparing the positive electrode material according to the third aspect, the preparation method comprising the following steps:

[0036] The nanometer-scale positive electrode material precursor is mixed with lithium salt and then calcined to obtain the positive electrode material.

[0037] The calcination comprises: a primary calcination, tableting the product of the primary calcination and then performing a secondary calcination;

[0038] Preferably, the primary calcination temperature is 400°C to 500°C, for example, 400°C, 425°C, 430°C, 435°C, 440°C, 460°C, 470°C, 480°C, 490°C or 500°C.

[0039] Preferably, the primary calcination time is 3 h to 6 h, for example, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h or 6 h.

[0040] Preferably, the temperature of the secondary calcination is 800°C to 950°C, for example, it may be 800°C, 825°C, 850°C, 870°C, 880°C, 900°C, 915°C, 930°C, 940°C or 950°C.

[0041] Preferably, the secondary calcination time is 8 h to 14 h, for example, it can be 8 h, 8.5 h, 9 h, 9.5 h, 10 h, 10.5 h, 11 h, 11.5 h, 12 h, 12.5 h, 13 h, 13.5 h or 14 h.

[0042] Preferably, the product of the secondary calcination is quenched after the secondary calcination is completed.

[0043] In a fifth aspect, the present invention provides an all-solid-state battery, comprising the positive electrode material described in the third aspect.

[0044] In one embodiment, the all-solid-state battery includes a positive electrode, a solid electrolyte layer and a negative electrode, wherein the positive electrode includes a positive electrode material, a solid electrolyte and a conductive agent.

[0045] In one embodiment, the present invention provides a method for preparing an all-solid-state battery, comprising the following steps:

[0046] In an atmosphere of protective gas, a mixed positive electrode powder is evenly distributed at the bottom of the mold, wherein the mixed positive electrode powder includes a positive electrode material, a first solid electrolyte and a conductive agent, and then a second solid electrolyte powder is added on the mixed positive electrode powder, and then a negative electrode material is evenly distributed on the second solid electrolyte powder. Pressure is applied to the upper and lower ends of the mold and the pressure is maintained to obtain an all-solid-state battery.

[0047] In one embodiment, the diameter of the mold is 8 mm to 15 mm, for example, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm or 15 mm. The amount of the mixed positive electrode powder is 5 mg to 10 mg, for example, 5 g, 5.5 g, 6 g, 7 g, 7.5 g, 8 g, 8.5 g, 9 g or 10 g.

[0048] In one embodiment, the mass ratio of the mixed positive electrode powder, the first solid electrolyte and the negative electrode material is (5-10): (70-90): (20-40), wherein the selection range of the mixed positive electrode powder is "5-10", for example, it can be 5, 5.5, 6, 7, 7.5, 8, 8.5, 9 or 10, etc.; the selection range of the first solid electrolyte is "70-90", for example, it can be 70, 71, 72, 73, 75, 76, 78, 80, 82, 83, 85, 86, 88 or 90, etc.; the selection range of the negative electrode material is "20-40", for example, it can be 20, 21, 22, 23, 25, 26, 27, 29, 30, 32, 33, 35, 36, 38 or 40, etc.

[0049] In one embodiment, the negative electrode material is a LiIn alloy film with a molar ratio of In to Li of 3:1.

[0050] In one embodiment, the magnitude of the applied pressure is 2T to 4T, for example, it may be 2T, 2.2T, 2.4T, 2.5T, 2.6T, 2.8T, 3T, 3.3T, 3.5T, 3.7T, 3.8T or 4T.

[0051] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] (1) The method of the present invention prepares a nanoscale positive electrode material precursor by using a spray pyrolysis method. The spray entering from the top sequentially experiences an upper temperature zone, a middle temperature zone, and a lower temperature zone under the action of gravity, and the temperature of the spray pyrolysis is increased, so a nanoscale positive electrode material precursor can be obtained. Since the particle size of the positive electrode material precursor is small, the positive electrode material prepared by using it can be applied to solid-state batteries to improve the contact between the positive electrode and the solid electrolyte, greatly improve the conductivity and lithium ion transmission rate, improve the material activity and capacity, and improve the performance of the solid-state battery.

[0054] (2) The method of the present invention simplifies the production process, the preparation method is pollution-free, the preparation time is short, the output is large, the cost is low, and it is suitable for large-scale production. Moreover, the prepared positive electrode material precursor has a small particle size and a narrow particle size distribution. Moreover, the preparation method of the present invention is suitable for doping nano-scale positive electrode material precursors, and the doping is easy and the element distribution uniformity is good. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 It is a schematic diagram of the structure of a spray pyrolysis device used in one embodiment of the present invention.

[0056] Figure 2 This is a scanned image of the nanoscale positive electrode material precursor prepared in Example 1. DETAILED DESCRIPTION

[0057] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.

[0058] The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0059] Example 1

[0060] This embodiment provides a method for preparing a nano-scale positive electrode material precursor, using a spray pyrolysis device to prepare a nano-scale positive electrode material for an all-solid-state battery. Figure 1As shown, the spray pyrolysis device includes a pyrolysis furnace 3, a furnace 4 is provided in the pyrolysis furnace 3, a nozzle 9 is provided on the top of the furnace 4, and a product outlet is provided at the bottom of the pyrolysis furnace 3; the pyrolysis furnace is divided into an upper temperature zone A, a middle temperature zone B and a lower temperature zone C with independent temperature control from top to bottom, and the height ratio of the upper temperature zone, the middle temperature zone and the lower temperature zone is 1:2:1, the upper temperature zone A and the middle temperature zone B are heated by electricity, and the lower temperature zone is heated by natural gas;

[0061] The spray pyrolysis device further comprises an air compressor 1, wherein the air compressor 1 is connected to a liquid storage bottle 2 and the nozzle 9 respectively, wherein the liquid storage bottle 2 is used to hold a mixed metal salt solution, wherein a first valve is provided on the pipeline between the air compressor 1 and the liquid storage bottle 2, and a second valve is provided on the pipeline between the air compressor 1 and the nozzle 9, and the atomization degree of the mixed metal salt solution can be adjusted by adjusting the first valve and the second valve;

[0062] The spray pyrolysis device also includes a cyclone separator 5, a collecting bottle 6, a blowing and suction dual-purpose extension 7 and an exhaust gas treatment device 8. The inlet of the cyclone separator 5 is connected to the product outlet, the outlet of the cyclone separator 5 is connected to the collecting bottle 6, the exhaust gas treatment device 8 is connected to the inlet of the cyclone separator 5, and a blowing and suction dual-purpose fan 7 is provided on the connecting pipeline between the exhaust gas treatment device 8 and the cyclone separator 5.

[0063] The preparation method comprises the following steps:

[0064] A nickel-cobalt-manganese ternary mixed salt solution (nickel, cobalt and manganese are all derived from sulfate, and the molar ratio of nickel, cobalt and manganese is 95:4:1) with a concentration of 150g / L is poured into the liquid storage bottle 2 and mixed evenly. Under the action of pressure, the ternary mixed salt solution in the liquid storage bottle 2 is atomized into tiny droplets through the nozzle 9 and sprayed into the furnace 4 of the pyrolysis furnace 3. The feed pressure is 0.3MPa, the angle of the nozzle is 30°C, the spray volume is 80mL / min, the pressure in the pyrolysis furnace is -0.3MPa, the temperature of the upper temperature zone A is 450°C, the temperature of the middle temperature zone B is 700°C, and the temperature of the lower temperature zone C is 1300°C. The atomized droplets are rapidly dehydrated, and pyrolysis and drying reactions occur to generate products. Under the gravitational force of the fan, they reach the cyclone separator 5 for sampling, and the samples are collected in the collection bottle 6 to obtain the ternary precursor oxide, that is, the nano-scale positive electrode material precursor.

[0065] Figure 2 This is a scanned image of the nanoscale positive electrode material precursor prepared in Example 1. It can be seen from the image that the primary particle size of the positive electrode material precursor is in the range of 3nm to 7nm, and the secondary particle size is in the range of 30nm to 70nm.

[0066] The present embodiment also provides a positive electrode material, and its preparation method includes the following steps: using the above-mentioned nano-scale positive electrode material precursor and lithium carbonate to mix at a molar ratio of Li:M (M is the metal element in the nano-scale positive electrode material precursor) = 1.05, calcining at 450°C for 5 hours in an air atmosphere; pressing the obtained sintered product into a compact and dense sheet, and then sintering at 900°C for 11 hours, and immediately quenching with liquid nitrogen after the sintering is completed, so as to obtain the positive electrode material.

[0067] Example 2

[0068] The difference from Example 1 is that during the preparation of the nanoscale positive electrode material precursor, the feed pressure is 0.5 MPa and the pressure in the pyrolysis furnace is -0.5 MPa.

[0069] Example 3

[0070] The difference from Example 1 is that during the preparation of the nano-scale positive electrode material precursor, the temperature of the upper temperature zone of the pyrolysis furnace is 400°C, the temperature of the middle temperature zone is 700°C, and the temperature of the lower temperature zone is 1000°C.

[0071] Example 4

[0072] The difference from Example 1 is that in the preparation process of the nanoscale positive electrode material precursor, nickel, cobalt and manganese are all derived from acetate.

[0073] Example 5

[0074] The difference from Example 1 is that during the preparation of the nanoscale positive electrode material precursor, the nozzle angle is 60°.

[0075] Example 6

[0076] The difference between this embodiment and embodiment 1 is that the preparation method comprises the following steps:

[0077] A nickel-cobalt-manganese ternary mixed salt solution (nickel, cobalt and manganese are all derived from sulfate, and the molar ratio of nickel, cobalt and manganese is 95:4:1) with a concentration of 110g / L is poured into the liquid storage bottle 2 and mixed evenly. Under the action of pressure, the ternary mixed salt solution in the liquid storage bottle 2 is atomized into tiny droplets through the nozzle 9 and sprayed into the furnace 4 of the pyrolysis furnace 3. The feed pressure is 0.5MPa, the angle of the nozzle is 45°C, the spray volume is 55mL / min, the pressure in the pyrolysis furnace is -0.5MPa, the temperature of the upper temperature zone A is 500°C, the temperature of the middle temperature zone B is 800°C, and the temperature of the lower temperature zone C is 1200°C. The atomized droplets are rapidly dehydrated, and pyrolysis and drying reactions occur to generate products. Under the gravitational force of the fan, they reach the cyclone separator 5 for sampling, and the samples are collected in the collection bottle 6 to obtain the ternary precursor oxide, that is, the nano-scale positive electrode material precursor.

[0078] Example 7

[0079] The difference from Example 1 is that the angle of the nozzle is 20°.

[0080] Comparative Example 1

[0081] The difference from Example 1 is that the temperatures of the upper temperature zone, the middle temperature zone and the lower temperature zone are all 700°C.

[0082] Comparative Example 2

[0083] The difference from Example 1 is that the temperatures of the upper temperature zone, the middle temperature zone and the lower temperature zone are all 1300°C.

[0084] Comparative Example 3

[0085] The difference from Example 1 is that the temperatures of the upper temperature zone, the middle temperature zone and the lower temperature zone are all 1300°C, 700°C and 450°C, and the nozzle atomization occurs at the bottom of the pyrolysis furnace, while sampling and collection are carried out at the top of the pyrolysis furnace.

[0086] The positive electrode materials prepared in Examples 1-6 and Comparative Examples 1-3 are used to assemble an all-solid-state battery in the following manner:

[0087] Under Ar gas atmosphere, 8 mg of mixed positive electrode powder (the mixed positive electrode powder is composed of positive electrode material, Li3InCl6 and Super P, and Li3InCl6 and Super P are purchased) is evenly distributed on the bottom of an all-solid-state mold made of PTFE with an inner diameter of 10 mm, and then 80 mg of Li6PS5Cl powder (purchased) is added on the mixed positive electrode powder, and then 30 mg of negative electrode material (the negative electrode material is a LiIn alloy film with a molar ratio of In to Li of 3:1, purchased) is evenly distributed on the Li6PS5Cl powder. Finally, a pressure of 3T is applied to the upper and lower ends of the all-solid-state mold and the pressure is maintained to fix it, thereby assembling a lithium-rich all-solid-state battery.

[0088] Performance Test:

[0089] The Blue Electric test system was used to test the capacity retention rate of the all-solid-state battery after 50 cycles at a voltage range of 3.6-4.2V and a rate of 0.1C. The calculation formula = discharge capacity at the 50th cycle / first discharge capacity × 100%.

[0090] See Table 1 for the results.

[0091] Table 1

[0092]

[0093]

[0094] As can be seen from Table 1, the positive electrode material prepared by the nanoscale positive electrode material precursor of the present invention can be applied to solid-state batteries to improve the contact between the positive electrode and the solid electrolyte, greatly improve the conductivity and lithium ion transmission rate, improve the material activity and capacity, and improve the performance of the solid-state battery.

[0095] At the same time, by comparing Example 1 with Example 7, it can be seen that if the angle of the nozzle is too small, the sprayed droplets are too large, resulting in incomplete calcination and reduced electrochemical properties of the material.

[0096] By comparing Example 1 with Comparative Examples 1-2, it can be seen that if the temperatures of the three temperature zones are set to be the same, the quality of the positive electrode material precursor will be reduced, which is not conducive to the electrochemical performance of the battery.

[0097] By comparing Example 1 with Comparative Example 3, it can be seen that if the method of spraying materials from the bottom is adopted, because the materials stay in the furnace for a long time, the continuous high temperature will cause serious lithium-nickel mixing and reduce the performance of the positive electrode material.

[0098] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a nanoscale positive electrode material precursor, characterized in that: A spray pyrolysis device is used to prepare nano-scale all-solid-state battery positive electrode materials, wherein the spray pyrolysis device comprises a pyrolysis furnace, and a nozzle is arranged on the top of the furnace of the pyrolysis furnace; the pyrolysis furnace is divided from top to bottom into an upper temperature zone, a middle temperature zone and a lower temperature zone with independent temperature control; The preparation method comprises the following steps: The mixed metal salt solution is sprayed through a nozzle, and the atomized droplets enter a pyrolysis furnace for spray pyrolysis. The temperature of the upper temperature zone is controlled to be t1 < the temperature of the middle temperature zone t2 < the temperature of the lower temperature zone t3. After spray pyrolysis, a nano-scale positive electrode material precursor is obtained.

2. The preparation method according to claim 1, characterized in that: t2-t1 is 200℃~300℃; Preferably, t3-t2 is 200°C to 400°C; Preferably, the temperature t1 of the upper temperature zone is 400°C to 500°C; Preferably, the temperature t2 of the medium temperature zone is 700°C to 800°C; Preferably, the temperature t3 of the lower temperature zone is 1000°C to 1300°C; Preferably, the ratio of the heights of the upper temperature zone, the middle temperature zone and the lower temperature zone is (1-1.5):(2-4):(1-1.5).

3. The preparation method according to claim 1 or 2, characterized in that: The mixed metal salt solution is a nickel-cobalt-manganese ternary mixed salt solution, and the concentration of the mixed metal salt solution is 100 g / L to 150 g / L; Preferably, the spray volume of the nozzle is 50 mL / min to 100 mL / min; Preferably, the angle of the nozzle is 30° to 120°; Preferably, under the action of pressure, the mixed metal salt solution enters the nozzle to be sprayed, and the feed pressure is 0.2MPa to 0.6MPa.

4. The preparation method according to any one of claims 1 to 3, characterized in that The spray pyrolysis device also includes an air compressor, which is connected to a liquid storage bottle and the nozzle respectively, and the liquid storage bottle is used to hold a mixed metal salt solution. A first valve is provided on the pipeline between the air compressor and the liquid storage bottle, and a second valve is provided on the pipeline between the air compressor and the nozzle. The atomization degree of the mixed metal salt solution can be adjusted by adjusting the first valve and the second valve; preferably, during the spray pyrolysis process, the pressure in the furnace is -0.1MPa to -0.6MPa.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The spray pyrolysis time is 5s to 10s.

6. A nanoscale positive electrode material precursor prepared by the method according to any one of claims 1 to 5, wherein the primary particle size of the nanoscale positive electrode material precursor is in the range of 3nm to 7nm, and the secondary particle size is in the range of 30nm to 70nm.

7. A positive electrode material, characterized in that: The positive electrode material is prepared using the nanoscale positive electrode material precursor described in claim 6.

8. A method for preparing a positive electrode material as claimed in claim 7, characterized in that: The preparation method comprises the following steps: The nanometer-scale positive electrode material precursor is mixed with lithium salt and then calcined to obtain the positive electrode material.

9. The preparation method according to claim 8, characterized in that: The calcination comprises: a primary calcination, tableting the product of the primary calcination and then performing a secondary calcination; Preferably, the primary calcination temperature is 400°C to 500°C; Preferably, the time of the first calcination is 3h to 6h; Preferably, the temperature of the secondary calcination is 800°C to 950°C; Preferably, the secondary calcination time is 8h to 14h; Preferably, the product of the secondary calcination is quenched after the secondary calcination is completed.

10. An all-solid-state battery, characterized in that: The all-solid-state battery comprises the positive electrode material according to claim 7.

Citation Information

Patent Citations

  • Nano-micron spherical powder and preparation method and equipment thereof

    CN113371682A

  • Spray pyrolysis equipment, method for preparing positive electrode material precursor and application

    CN118162053A

  • High-entropy sodium battery positive electrode precursor as well as preparation method and application thereof

    CN118183874A

  • Copper-iron-manganese-based sodium electric precursor as well as preparation method and application thereof

    CN118419983A

  • Spray Pyrolysis Synthesis of Mesoporous Positive Electrode Materials for High Energy Lithium-Ion Batteries

    US20120282522A1